Cardiac and extracardiac complications during CTO interventions: prevention and management. (June 2010) - Favero, Luca; Penzo, Carlo; Nikas, Dimitrios; Pacchioni, Andrea; Pasquetto, Gianpaolo; Saccà, Salvatore; Reimers, Bernhard
Percutaneous coronary intervention of chronic total occlusion carries the risk of severe complications that are responsible for a significant morbidity and mortality rate associated with these procedures. Complications may be cardiac, such as acute myocardial infarction and coronary perforation, or extracardiac, such as aortic dissection, contrast-induced nephropathy and radiation skin injuries. The mechanisms, prevention and treatment of complications associated with percutaneous coronary intervention of chronic total occlusion are reviewed in this article.